CONTROL OF THE QUALITY OF VEGETABLE OILS AND ENRICHMENT WITH BIOACTIVE SUBSTANCES - D.O.Otanazarova; D.T.Ruzmetova (USA- SCIENTIFIC REVIEW OF THE PROBLEMS AND PROSPECTS OF MODERN SCIENCE AND EDUCATION, 2025)
The increase in the world population indicates that efficient use of food resources, and at the same time, providing people with high-quality, safe, and beneficial products that fully preserve their nutritional value, is one of the most important issues of today. Taking this issue into account, research was conducted on checking the quality of vegetable oils currently offered for public consumption. The analysis of vegetable oils offered for consumption showed that the peroxide value of every 10 analyzed samples was determined to be from 10.71 mmol/kg ½ O to 17.22 mmol/kg ½ O, respectively. This means that, despite not having expired, all analyzed samples contain primary oxidation products 2–3 times higher than the standard required by state regulation. From this, it follows that oxidation processes have already begun in the analyzed vegetable oil samples offered for consumption. Considering that oxidation in vegetable oils proceeds through a chain reaction, we can conclude that even during the valid shelf life period, these vegetable oils already contain primary and secondary oxidation products dangerous to human health. Prooxidants that triggered oxidation in vegetable oils or the causes of the beginning of oxidation in oils could have affected the product at any stage—during production, storage, delivery, or in commercial complexes. To preserve the quality and nutritional value of vegetable oils, it is necessary to introduce antioxidants into the production process to prevent oxidation, thereby preventing the appearance of primary, secondary, and tertiary oxidation products dangerous to human health in vegetable oils offered for consumption by applying natural antioxidants in the production process